Modern Research and Prospects for the Use of Creeping Anchors – Tribulus Terrestris L (Texas Journal of Agriculture and Biological Sciences, 2023)
The article describes the biology, morphology, growth and pharmacological properties of the annual herbaceous plant Tribulus terrestris L. The botanical description, classification of the genus, distribution, chemical composition, application in folk medicine, cosmetology, historical information, as well as application in traditional medicine and drugs used in medicine are given.